Approaches for computing test‐case‐aware covering arrays. (16th September 2018) - Koc, Ugur; Yilmaz, Cemal
Summary: Test‐case‐aware covering arrays have been recently introduced to overcome the shortcomings of standard covering arrays, which prevent some combinations of option settings from being exercised in the presence of test‐case‐specific constraints. A number of proof‐of‐concept approaches for computing test‐case‐aware covering arrays have also been presented in the aforementioned work. The main concern in the development of these approaches was neither their efficiency nor their effectiveness, but their correctness. On the other hand, efficient and effective ways of computing test‐case‐aware covering arrays are of great practical importance. To improve the applicability of test‐case‐aware covering arrays in practice, this work presents a number of efficient and effective approaches for computing them. Furthermore, the proposed approaches are evaluated by conducting a set of experiments on widely‐used highly‐configurable software systems and comparing their efficiency and effectiveness to those of the existing approaches in various practical testing scenarios. Abstract : 16 constructors for computing test case‐aware covering arrays. Empirical evaluations on widely‐used highly‐configurable systems using 3 practical scenarios. Significantly smaller covering arrays at comparable or lower costs. Making test case‐aware covering arrays more practical.